Pengetahuan, Sikap dan Dukungan Keluarga terhadap Niat Memeriksakan Dahak pada Presumtif TBC - Nike Indah Arodah; Noor Alis Setiyadi (Journal of Telenursing (JOTING), 2023)
This study aims to determine the relationship between knowledge, attitudes, and family support on the intention to have sputum examined in a group suspected of having tuberculosis in the Margoyoso II Health Center. The research method used in this research is quantitative. The design in this study is analytic with a cross sectional approach. The results showed that of the 113 respondents who had low knowledge about tuberculosis, 44 (67.7%) had a low attitude towards sputum examination, 47 (65.3%), and 55 (85.9%) had a low level of family support. Results The knowledge variable has a p value of 0.003, attitude has a p value of 0.006, family support has a p value <0.0001. The results of the probability variables of knowledge, attitudes, and family support are smaller than the significant level of 5% (0.05), meaning that it can be concluded that there is a relationship related to knowledge, attitudes, and family support on the intention to check sputum in the suspected tuberculosis group in the Work Area of ​​the Margoyoso II Health Center . Keywords: Attitude, Family Support, Knowledge, Sputum Examination, Tuberculosis